Determination of Young's modulus and yield strength of porous low-k dielectric films by nanoindentation under complete consideration of the substrate influence. (2nd April 2009) - Herrmann, M.; Richter, F.
The capabilities of the 'effective indenter method' with respect to the characterisation of porous xerogel thin films have been investigated using samples with porosities ranging from 43% to 57%. Young's modulus of the samples was decreasing from 2.67 GPa to 0.83 GPa with growing porosity. Yield strength was determined using spherical indentation data. With a larger indenter (R = 48 μm) the 'effective indenter method' could be directly applied while for a smaller one (R = 4.2 μm) the 'effective indenter extrapolation method' had to be utilised to account for the larger amount of plastic deformation. Both approaches delivered the same yield strength decreasing from (140 ± 5) MPa to (75 ± 3) MPa with increasing porosity.